2004
DOI: 10.1038/sj.bjc.6601821
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer risk among first-generation migrants in the Netherlands

Abstract: We investigated breast cancer incidence in migrants in the Netherlands in 1988 -1998. The standardised incidence ratio for breast cancer in Northwest-Netherlands was statistically significantly reduced for women born in Surinam (0.56), Turkey (0.29) and Morocco (0.22). The proportion of women with advanced stages (III and IV) did not differ significantly between migrants and women born in the Netherlands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 6 publications
4
22
0
Order By: Relevance
“…This demonstrates the importance of using a regional or national correction factor for self-selection, where possible. Factors which could be associated with lower breast cancer risk factors in unscreened women in Limburg are unclear, but could for example be due to a lower number of relatives with a history of breast cancer, to differences in socio-economic status, to ethnicity, or to screening outside the screening program in unscreened women [13,14,[21][22][23][24]. Further research should explore the background of the lower baseline risk for breast cancer death in unscreened women in the IKL-region.…”
Section: Number Of Case-referent Setsmentioning
confidence: 89%
“…This demonstrates the importance of using a regional or national correction factor for self-selection, where possible. Factors which could be associated with lower breast cancer risk factors in unscreened women in Limburg are unclear, but could for example be due to a lower number of relatives with a history of breast cancer, to differences in socio-economic status, to ethnicity, or to screening outside the screening program in unscreened women [13,14,[21][22][23][24]. Further research should explore the background of the lower baseline risk for breast cancer death in unscreened women in the IKL-region.…”
Section: Number Of Case-referent Setsmentioning
confidence: 89%
“…33 Such evidence was consistent among Polish immigrants in France, 34 immigrants from England and Wales in New Zealand and vice versa, 35 African immigrants in UK, 30 France 28,29 and the Netherlands. 27 However, among Italian emigrants to South America, the risk of cervical cancer increased after migration to the high-risk areas. 36 The establishment of an efficient cervical cancer screening program in Sweden 9 also needs to be considered when interpreting our results.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28][29][30][31] However, they mainly analysed cervical cancer mortality 22-24,28-31 and had no information about the exact migration date, age at migration [22][23][24]26,27,29,31 or SES 13,19,20,23,24,26,27 Moreover, the effect of time spent in the host country on risk of cervical cancer has not been studied conclusively to date. 32 Our findings support the overall conclusions of previous studies that cervical cancer risk or mortality is lower among immigrants than in their countries of origin.…”
Section: Discussionmentioning
confidence: 99%
“…We found that significantly fewer immigrants were seen for cancer genetic counseling than would be expected from data on the general population. Next to possible confounding factors like lower socioeconomic status (Culver et al 2001;Chin et al 2005), low level of acculturation (Heck et al 2008) and traditional beliefs (Barlow-Stewart et al 2006), the low number of immigrants can partly be explained by the lower incidence of cancer and cancer mortality rates in different countries of origin (Turkey, Morocco, Surinam, Netherlands Antilles and Aruba) when compared to the Netherlands (Arnold et al 2011;Stirbu et al 2006;Visser et al 2004). However, since specific approaches to immigrant populations improve their access to genetic counseling, as shown for the enrolment of African-American families in a genetic research project in the USA (Spruill 2010), we still recommend future studies to look carefully at the reasons why immigrants are not referred for counseling.…”
Section: Discussionmentioning
confidence: 99%